Interactive Narrative Simulation as a Method for Preceptor Development - Charlene R. Williams; Robert Hubal; Michael D. Wolcott; Abbey Kruse (MDPI AG, 2021)
(1) Background: This proof-of-concept study assessed an interactive web-based tool simulating three challenging non-academic learning situations-student professionalism, cross-cultural interactions, and student well-being-as a means of preceptor development. (2) Methods: Three scripts focused on professionalism, cross-cultural interactions, and student well-being were developed and implemented using a commercial narrative tool with branching dialog. Delivered online, this tool presented each challenge to participants. Participants had up to four response options at each turn of the conversation; the choice of response influenced the subsequent conversation, including coaching provided at the resolution of the situation. Participants were invited to complete pre-activity, immediate post-activity, and one-month follow-up questionnaires to assess satisfaction, self-efficacy, engagement, and knowledge change with the tool. Knowledge was assessed through situational judgment tests (SJTs). (3) Results: Thirty-two pharmacist preceptors participated. The frequency of participants reflecting on challenging learning situations increased significantly one-month post-simulation. Participants affirmatively responded that the tool was time-efficient, represented similar challenges they encountered in precepting, was easily navigable, and resulted in learning. Self-efficacy with skills in managing challenging learning situations increased significantly immediately post-simulation and at a one-month follow-up. Knowledge as measured through SJTs was not significantly changed. (4) Conclusions: Preceptors found an interactive narrative simulation a relevant, time-efficient approach for preceptor development for challenging non-academic learning situations. Post-simulation, preceptors more frequently reflected on challenging learning situations, implying behavior change. Self-efficacy and self-report of knowledge increased. Future research is needed regarding knowledge assessments.